Crystallization and preliminary X-ray crystallographic studies of fatty acid-CoA racemase from Mycobacterium tuberculosis H37Rv - Rhee, Kyung-Hee (International Union of Crystallography, 2005)
Fatty acid-CoA racemase plays an important role in the β-oxidation of branched-chain fatty acids and fatty-acid derivatives as it catalyzes the conversion of several (2R)-branched-chain fatty acid-CoAs to their (2S)-stereoisomers. Fatty acid-CoA racemase from Mycobacterium tuberculosis H37Rv has been purified to homogeneity and crystallized by the hanging-drop vapour-diffusion method with polyethylene glycol 4000 as precipitant. The crystals belong to the trigonal space group P3(1) or P3(2), with unit-cell parameters a = b = 109.56, c = 147.97 Å. The asymmetric unit contains six monomers, corresponding to a V (M) value of 2.15 Å(3) Da(−1). A complete native data set has been collected at 2.7 Å resolution using a synchrotron-radiation source.